Academic Cyberloafing and Learning Concentration Among Nursing Students: A Case Study - Rohita, Tita; Rohwina, Rohwina (Jurnal Pendidikan Keperawatan Indonesia, 2025)
Introduction: The advancement of digital technology has significantly transformed the learning environment, offering both opportunities and challenges. One emerging challenge is academic cyberloafing non-academic internet use during learning activities which may negatively impact students' concentration. Objective: This study analyzes academic cyberloafing as a challenge to learning concentration among nursing students at the Faculty of Health Sciences, Universitas Galuh, in 2025. Method: Using a non-experimental, correlational quantitative method with a cross-sectional design, the research was grounded in Akbulut’s five dimensions of academic cyberloafing and Bloom’s three aspects of learning concentration. Data were collected through an online Likert-scale questionnaire distributed to 74 purposively selected respondents from a population of 278 active nursing students. Result: The majority of respondents were female (70.3%) and aged 19–21 years (59.5%), with a relatively even distribution across all academic years. Most students showed moderate levels of academic cyberloafing (74.3%) and moderate learning concentration (64.9%). Statistical analysis using the Spearman Rank test showed a significant negative correlation between academic cyberloafing and learning concentration (r = –0.492, p = 0.000), indicating that higher levels of cyberloafing are associated with lower levels of concentration. This result indicates a moderate negative correlation between academic cyberloafing and learning concentration (r = –0.492). Conclusion: These findings highlight academic cyberloafing as a key challenge in maintaining student focus and suggest the importance of implementing adaptive learning strategies, enhancing digital literacy, and regulating non-academic technology use within the educational environment.